Effect of nanonization on physicochemical, sensory, and nutritional properties of Ginger (Zingiber officinale) and Sappan Wood (Caesalpinia sappan) powdered drink - Adhila Fayasari; Mia Srimiati; Gina Tsania Al Madany; Aji Humaedi; Etyca Rizky Yanti (AcTion: Aceh Nutrition Journal, 2026)
Ginger and sappanwood contain high levels of antioxidants with recognized immunomodulatory and antidiabetic properties; however, their bioavailability is limited. Nanonization has the potential to enhance absorption by reducing the particle size. This study evaluated the differences in the physicochemical, sensory, and nutritional properties of nano and non-nano ginger–sappanwood powdered drink formulations. A completely randomized design (CRD) with four ratios (F1:50:40, F2:60:40, F3:70:30, and F4:80:20) was applied, and the formulations were processed into powders and powdered drinks. Sensory evaluation was conducted using semi-trained panelists. The proximate composition and antioxidant activity were determined. Statistical differences were analyzed using two-way analysis of variance (ANOVA) (α = 0.05). Nano-milling improved sensory attributes in the powder form, particularly color and texture (p < 0.05). Differences in flavor were observed only in the drink form, whereas taste and overall acceptability were not significantly affected. Formula 4 (80:20) achieved the highest hedonic and organoleptic ratings. Antioxidant activity was generally low across all formulations; however, the nano-milled powders exhibited slightly higher values than their non-nano counterparts. In conclusion, nanonization enhanced selected sensory qualities and modestly improved antioxidant performance, particularly in the powdered form.